Multiple co‐occurrent alien invaders constrain aquatic biodiversity in rivers. Issue 6 (13th July 2021) - Guareschi, Simone; Laini, Alex; England, Judy; Barrett, Jon; Wood, Paul J.
Abstract: A greater understanding and effective management of biological invasions is a priority for biodiversity conservation globally. Many freshwater ecosystems are experiencing the colonization and spread of multiple co‐occurrent alien species. Here the implications of both the relative abundance and richness of alien invaders on aquatic macroinvertebrate taxonomic and functional richness, ecosystem quality, and functional redundancy are assessed using long‐term data from rivers in England. Based on the most common aquatic invaders, results indicated that their richness, rather than abundance, was the most important factor negatively affecting aquatic macroinvertebrate biodiversity. However, the response of functional redundancy was negatively affected by invader abundance at the river basin scale. The response of communities varied as the number of invading taxa increased, with the most marked reductions following the colonization of the first few invaders. Results indicate that different facets of multiple biological invasions influence distinct aspects of aquatic biodiversity. Preventing the establishment of new invaders and limiting invader taxa richness within a community should therefore be a conservation priority. These findings will assist river scientists in understanding mechanisms driving changes in biodiversity and facilitate the testing of ecological theories while also ensuring environmental managers and regulators can prioritize conservation / management opportunities.